Предмет: Алгебра,
автор: rtatana114
![2cos {}^{2} 2x + 3cos {}^{2} x = 2 2cos {}^{2} 2x + 3cos {}^{2} x = 2](https://tex.z-dn.net/?f=2cos+%7B%7D%5E%7B2%7D+2x+%2B+3cos+%7B%7D%5E%7B2%7D+x+%3D+2)
Ответы
Автор ответа:
0
Ответ:
Объяснение:
2(cos2x)(cos2x) +3(cosx)^2 = 2
2((cosx)^2 - (sinx)^2)^2 + 3(cosx)^2 = 2
2(2(cosx)^2 - 1)^2 + 3(cosx)^2 = 2
2(4(cosx)^4 - 4(cosx)^2 + 1) + 3(cosx)^2 = 2
8(cosx)^4 - 5(cosx)^2 = 0
(cosx)^2 * (8(cosx)^2 - 5) = 0
cosx = 0 => x = pi/2 + pi*n, n - целое число.
(cosx)^2 = 5/8 => cosx = sqrt(5/8); cosx = -sqrt(5/8) => x = arccos(sqrt(5/8)) + 2pi*k, k - целое число. x = -arccos(sqrt(5/8)) + 2pi*m, m - целое число.
Можно еще вынести из под корня 2 и оставить под корнем 2 вместо 8.
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: g32416132
Предмет: Математика,
автор: ната919